Analyzing Information about a Hajj Pilgrimage in Indonesia in the Rare Newspaper Collection of The National Library of Indonesia - Supratman, Frial Ramadhan (Record and Library Journal, 2020)
Background of the study: Indonesia is a country whose the largest number of Muslims in the world.Â  Every year, many Indonesian Muslims come to Mecca to perform hajj pilgrimage. In order to improve pilgrimage activity, Government and society need exact information about that. The librarian can take an important role in order to supply information about hajj pilgrimage.Purpose: The aim of research is explaining description and information about Indonesian hajj pilgrims through a collection of rare newspapers in the National Library of Indonesia.Method: The method used in this research is a descriptive research method. Author analyzes twenty two newspapers in National Library. Having been analyzed, the information obtained is interpreted by historical approach.Findings: The result of this research is that the author finds out 22 newspapers which contains information of hajj pilgrims. The information is qualitative data on the amount of hajj pilgrims and ships, the expense of hajj pilgrimage, the experience of hajj pilgrims, the problem faced by hajj pilgrims and government policy in controlling hajj pilgrims.Conclusion: In this paper, the author argues that rare newspaper collection contains many information about the activity of the hajj pilgrimage during Dutch colonial period.